Diseño de productos escolares coleccionables, impresos y multimedia, tomando como referente a los anfibios del parque Nacional Llanganates, dirigido a estudiantes de bachillerato de la Unidad Educativa Nacional Salcedo, de la ciudad de Salcedo. - Taipe Cevallos, Lisseth Natalí (2019)
This project aims to inform about the amphibian species of the Llanganates National Park generating a sense of belonging by the youth towards their natural environment. The absence of informative material about the endemic fauna of this reserve demanded the need to elaborate an analogous and multimedia proposal that reports on specific amphibians that require more attention due to their high risk of extinction, the destruction of their habitat or the rarity of their species, at the same time as entertaining and interacting with young people. The aim of this project is to develop informative material with a high visual, creative and interactive impact for high school students of the Salcedo Educative Unit. The methodology was focused on critical, informative and scientific aspects since an exhaustive morphological analysis of the amphibian species was carried out, which supported by a symbiosis system allowed to generate modular structures embodied in printed supports that reflect the multimedia Through a mobile device, the methodological design used was feedback through technological articulated. The technique applied was the survey which gave as a result the realization of collectable school materials. The project is very transcendental, since it is framed in informative aspects of the fauna present in the Llanganates National Park where diverse species in danger of extinction or others that ABSTRACT await to be studied live. The proposal contributes through a theme of primary interest for youth, knowledge, awareness and appreciation of their natural heritage based on multimedia technology which is on rise conducting visual elements and information in order to generate an awareness within the youth mentality about the care of the environment. Within technological aspects employed highlights the realization of augmented reality on school implements which provides a creative, dynamic and different in content, emphasizing that the information is practical, accurate and with an additional bonus, considering that the target audience seeks new information alternatives.